The impact of tax on foreign direct investment: empirical evidence and the implications for tax integration schemes - Devereux, M; Freeman, H (1995)
We estimate the impact of taxation on foreign direct investment (FDI) flows, using data on flows between seven countries for 1984 through 1989, and a sophisticated measure of the cost of capital. We find that the choice between domestic investment and total outward FDI is not significantly affected by taxation but that taxation does affect the location of outward FDI. These results are used to examine the impact of tax integration systems. Giving a tax credit to foreign shareholders may induce a large increase in inward FDI from exemption countries but not from partial-credit countries. For the United States, the total effect would be small.